Pengaruh Program Kesejahteraan Dan Komunikasi Organisasi Terhadap Semangat Kerja Karyawan: Studi Pada PT. Permata Hijau Sawit Medan - Vania Apriani Pakpahan; Feby Aulia Safrin (Pusat Riset dan Inovasi Nasional, 2024)
The company will retain employees who have high work morale. This is because employees who have work enthusiasm will contribute and be actively involved in the company's progress. Welfare programs and organizational communication are thought to be factors that have an influence on work morale. This research aims to analyze the influence of welfare programs and organizational communication on employee morale (study at PT. Permata Hijau Sawit Medan). The influence of the welfare program and organizational communication will be analyzed partially and simultaneously on employee morale. The form of research used for this research is quantitative with an associative approach. Sampling was carried out using a saturated sampling technique and used 40 respondents as samples. The results of the research conducted show that the welfare program variables (X1) and organizational communication (X2) have a significant effect on employee morale. The welfare program and organizational communication variables simultaneously influence employee morale (Y) with an R value of 0.955. Through the adjusted R square value, it is known that the welfare program and organizational communication variables contribute 91.2% to employee morale while 8.8% is influenced by the variables other.